Lack of Autophagy Induction by Lithium Decreases Neuroprotective Effects in the Striatum of Aged Rats - Angelica Jardim Costa; Adolfo Garcia Erustes; Rita Sinigaglia; Carlos Eduardo Neves Girardi; Gustavo José da Silva Pereira; Rodrigo Portes Ureshino; Soraya Soubhi Smaili (MDPI AG, 2021)
The pharmacological modulation of autophagy is considered a promising neuroprotective strategy. While it has been postulated that lithium regulates this cellular process, the age-related effects have not been fully elucidated. Here, we evaluated lithium-mediated neuroprotective effects in young and aged striatum. After determining the optimal experimental conditions for inducing autophagy in loco with lithium carbonate (Li2CO3), we measured cell viability, reactive oxygen species (ROS) generation and oxygen consumption with rat brain striatal slices from young and aged animals. In the young striatum, Li2CO3 increased tissue viability and decreased ROS generation. These positive effects were accompanied by enhanced levels of LC3-II, LAMP 1, Ambra 1 and Beclin-1 expression. In the aged striatum, Li2CO3 reduced the autophagic flux and increased the basal oxygen consumption rate. Ultrastructural changes in the striatum of aged rats that consumed Li2CO3 for 30 days included electrondense mitochondria with disarranged cristae and reduced normal mitochondria and lysosomes area. Our data show that the striatum from younger animals benefits from lithium-mediated neuroprotection, while the striatum of older rats does not. These findings should be considered when developing neuroprotective strategies involving the induction of autophagy in aging.